Accountings Implemented Evaluation on UMKM in Supporting Industrialization Program Bright NTB - Taufik Kurahman; Baiq Anggun Hilendri Lestari (International Journal of Asian Business and Management, 2024)
Accounting plays   an essential role in upturned UMKM,  since with a good accounting registry and according to accounting default already been established therefore gets helps the small enterprises in taking the right decision, water down   getting  a credit from creditors  , and gets to provide accurate information on time. Accounting constitutes to key to seeing the financial position and effort performance measurement that can spontaneously take benefit. This researcher utilizes descriptive research type qualitative to analyze data and information concerning all systems and their effort activity done by UMKM NTB bases SAK EMKM. Since a large part of UMKM    hasn't applied an accounting system based on SAK  UMKM,  therefore accounting implementation of financial statement representation for UMKM is still unclear which is with document transactions that often happen deep in its effort. SAK UMKM was applied by UMKM at  NTB  in particular at  Mataram  City in term accounting.  It  is  caused  because  agents  of UMKM still  utterly understood  the  importance  of SAK UMKM, it because of ignorance of SAK UMKM and its reduced socialization or training of government or UMKM supporting institute